Ultrasound-guided central vein cannulation - Cvetanovic, Vladan; Veselinovic, Ines; Dinic, Vesna; Nikolic, Aleksandar; Stojanovic, Milena; Markovic, Milica; Gmijović, Marko (Acta medicae Medianae, 2021)
Cannulation of large venous blood vessels is an important aspect of treating critically ill patients in terms of fluid administration, medication, parenteral nutrition, and monitoring. A conventional technique that uses superficial anatomy and palpation to identify large blood vessels before cannulation is based on the presumed localization of blood vessels, identification of anatomical features on the skin, and blind needle insertion until the time of blood aspiration. This technique is associated with a higher likelihood of failure, requiring more attempts and more complications. Ultrasound-guided vascular access provides a greater percentage of overall success as well as the success of the first cannulation attempt, faster vascular access, patient satisfaction and fewer complications.
Keywords: ultrasound, central venous catheters, cannulation